2010
DOI: 10.1103/physrevlett.104.171101
|View full text |Cite
|
Sign up to set email alerts
|

Wave-Vector Dependence of Magnetic-Turbulence Spectra in the Solar Wind

Abstract: Using four-point measurements of the Cluster spacecraft, the energy distribution was determined for magnetic field fluctuations in the solar wind directly in the three-dimensional wave-vector domain in the range |k| Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 24 publications
4
67
1
Order By: Relevance
“…Although this is consistent with linear Maxwell-Vlasov dispersion relations for very oblique KAWs (θ kB 0 = cos(k ·B 0 ) ≈ 88 • ), with such strong obliquities of the ks the results can also be interpreted as indicating the presence of relatively energetic quasi-two-dimensional turbulence. Indeed, Narita et al [71,72,76,77] use essentially the same multi-spacecraft technique, over similar wavenumber ranges, and state that they find no evidence of a linear dispersion relation. They favour an explanation in terms of well-developed strong quasi-two-dimensional turbulence.…”
Section: (A) Review Of Observationsmentioning
confidence: 99%
“…Although this is consistent with linear Maxwell-Vlasov dispersion relations for very oblique KAWs (θ kB 0 = cos(k ·B 0 ) ≈ 88 • ), with such strong obliquities of the ks the results can also be interpreted as indicating the presence of relatively energetic quasi-two-dimensional turbulence. Indeed, Narita et al [71,72,76,77] use essentially the same multi-spacecraft technique, over similar wavenumber ranges, and state that they find no evidence of a linear dispersion relation. They favour an explanation in terms of well-developed strong quasi-two-dimensional turbulence.…”
Section: (A) Review Of Observationsmentioning
confidence: 99%
“…On the other hand, observations also suggested that turbulence was present and may have contributed to heating [e.g., Coleman, 1968]. Subsequent observational studies indicated that at magnetohydrodynamic (MHD) scales there are at least two distinct types of fluctuation and that the wave-like energy may be a minor component Bieber et al, 1996;Milano et al, 2004;Dasso et al, 2005;Horbury et al, 2005Horbury et al, , 2008Podesta, 2009;Osman and Horbury, 2009;Narita et al, 2010]. This encouraged development of more complete transport theories for the energy-containing range quantities [e.g., Tu and Marsch, 1993;Matthaeus et al, 1994Matthaeus et al, , 1996Matthaeus et al, , 1999Matthaeus et al, , 2004Zank et al, 1996;Smith et al, 2001Smith et al, , 2006Isenberg et al, 2003Isenberg et al, , 2010aIsenberg, 2005;Breech et al, 2005Breech et al, , 2008Yokoi and Hamba, 2007;Usmanov and Goldstein, 2010;Ng et al, 2010], in which turbulence properties are built in, contrasting with WKB theory, in which the waves are noninteracting at leading order.…”
Section: Introductionmentioning
confidence: 99%
“…The situation is different in plasma turbulence where the existence of a mean magnetic field sets a natural preferential direction for anisotropy. Anisotropy is thus a key topic in theoretical [3][4][5], numerical [6,7], and observational studies of plasma turbulence in the solar wind [8][9][10][11][12][13].The seminal study of Belcher and Davis [8] used Mariner 5 observations to investigate anisotropy of the solar wind magnetic fluctuations in the low frequency (energy containing) and inertial intervals. They found that the fluctuations on average have 5 : 4 : 1 power anisotropy in an orthogonal coordinate system whose axis are [e B × e R , e B × (e B × e R ), e B ], where e B is a unit vector in the average magnetic field direction and e R is a unit vector radially away from the sun.…”
mentioning
confidence: 99%
“…The situation is different in plasma turbulence where the existence of a mean magnetic field sets a natural preferential direction for anisotropy. Anisotropy is thus a key topic in theoretical [3][4][5], numerical [6,7], and observational studies of plasma turbulence in the solar wind [8][9][10][11][12][13].…”
mentioning
confidence: 99%